Immunoreactive proteins of Saccharopolyspora rectivirgula for farmer's lung serodiagnosis. Issue 11 (4th November 2014) - Barrera, Coralie; Millon, Laurence; Rognon, Bénédicte; Quadroni, Manfredo; Roussel, Sandrine; Dalphin, Jean‐Charles; Court‐Fortune, Isabelle; Caillaud, Denis; Jouneau, Stephane; Fellrath, Jean‐Marc; Zaugg, Christophe; Reboux, Gabriel; et al.
<x xml:space="preserve">Abstract</x> Purpose Saccharopolyspora rectivirgula is the principal cause of farmer's lung disease (FLD). Serodiagnosis is based on immunoprecipitation techniques or enzyme immunoassays with homemade crude antigens and is not standardized. We aimed to produce specific recombinant antigens for the development of a standardized ELISA. Experimental design We recruited 41 patients and 43 healthy exposed controls from five university hospital pneumology departments in France and Switzerland. S. rectivirgula proteins were extracted, separated by 2D electrophoresis, and subjected to Western blotting, with sera from FLD patients or controls. FLD‐specific proteins were identified by MS and were produced as recombinant antigens. The diagnostic performance of ELISA tests using the recombinant antigens was assessed with all the sera from FLD patients and controls. Results We identified 25 FLD‐specific proteins, some of which play important roles in transport, nutrition, or virulence. We produced 17 of these proteins as recombinant antigens and assessed their suitability for inclusion in the ELISA test. A combination of three of these proteins (SR1FA, SR17, and SR22) proved remarkably effective at discriminating between patients and controls, with a sensitivity of 83% and a specificity of 77%. Conclusions and clinical relevance The recombinant antigens produced in this study constitute a major step toward the improvement of diagnostic performance and the standardization of FLD serodiagnosis.